Pengaruh Massa Dan Ukuran Partikel Adsorben Kulit Singkong Terhadap Penyisihan Kadar COD Dan BOD Pada Pengolahan Limbah Cair Tahu - Ade Rani Putri; Syarfi Daud; Shinta Elystia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
One of the treatments of reducing the pollutant level in tofu liquid waste is adsorption with cassava skin adsorbent. The objective of the study was to calculate the efficiency of minimizing of COD and BOD levels on the effluent treatment of tofu waste and to determine the appropriate adsorption isotherm. The fixed variable used in this study was stirring speed of 100 rpm and contact time 60 minutes. The main variable used consisted of a mass of adsorbent 1.5; 2 and 2.5 g and a particle measurement variation of -50+100; -100+170 and -170 mesh The highest removal efficiency of COD and BOD was 74.74% and 71.48% at 2.5 g mass with 170 mesh particle size. The type of isotherm that is suitable with the adsorption of COD and BOD content by cassava skin adsorbent is Freundlich isotherm with R2 value of 0.9875 for COD and 0.9971 for BOD. The highest metal removal efficiency of COD and BOD was 74.74% and 71.48% at 2.5 g mass with -170 mesh particle measurement. The type of isotherm that is suitable the adsorption of COD and BOD content by cassava skin adsorbent is Freundlich isotherm with R2 value of 0.9875 of COD and 0.9971 for BOD.Keywords: Adsorbent, Adsorption, BOD, COD, Cassava Skin, Tofu Liquid Waste